Handbook of Neuroevolution Through Erlang - Sher, Gene I. (Springer New York : Imprint: Springer, 2013)
Handbook of Neuroevolution Through Erlang presents both the theory behind, and the methodology of, developing a neuroevolutionary-based computational intelligence system using Erlang.With a foreword written by Joe Armstrong, this handbook offersan extensivetutorial forcreating a state of the art Topology and Weight Evolving Artificial Neural Network (TWEANN) platform. In a step-by-step format, the reader is guided from a single simulated neuron to a complete system. By following these steps, the reader will be able to use novel technology to build a TWEANN system, which can be applied to Artificial Life simulation, and Forex trading. Because of Erlangs architecture, it perfectly matches that of evolutionary and neurocomptational systems. As a programming language, it is a concurrent, message passing paradigm which allows the developers to make full use of the multi-core & multi-cpu systems. Handbook of Neuroevolution Through Erlang explains how to leverage Erlangs features in the field of machine learning, and the systems real world applications, ranging from algorithmic financial trading to artificial life and robotics.